Student's perception of storytorial - An innovative approach to self-learning - S A Priya; M S Sunitha; R Rajalakshmi; C M Ramya; Smitha Malenahalli Chandrashekarappa (Wolters Kluwer Medknow Publications, 2022)
Background: In the traditional undergraduate curriculum, majority of the hours is dedicated to passive lectures where students are mere listener. Emphasis on self-learning is restricted to reading some of the topics from the book and Internet. With reference to this, storytorial was introduced as an innovative learning method mainly concentrating on self-learning, communication skills, and retrieval of concept. A story was illustrated and enacted to a topic in physiology during tutorial hour, hence the name storytorial. Methods: This method of learning was introduced to the I MBBS 2018-2019 batch, comprising 200 students. They were divided into small groups; topics and list of students to perform storytorial were displayed in the notice board 15 days before the session. On the day of session, the selected 10 students performed a story that illustrated the physiology topic assigned to them. Time allotted for the presentation was 20-30 min. The students enacted the story, and one of them narrated how the story is linked to the topic. Later, a case study related to the topic was given, and the students solved the case in the presence of an in-charge teacher for that batch. The session lasted for 1 h. Likewise, all the students were involved in the performance with a different topic in separate sessions according to the time table. At the end of all the sessions, subjective feedback of storytorial from the students was taken using 5-point Likert scale and computed. Results: The analysis of feedback on 5-point Likert scale with point 5 as strongly agree and 1 as strongly disagree was as follows: increased confidence and learning - 4.468, better understanding of concept - 4.058, better memory retention and retrieval - 4.28, and enjoyed and liked the sessions - 4.37. 90% of the students recommended storytorial for the next batch. Conclusion: This innovative method is an extended role-play where the concepts are illustrated in the form of story which helps the students to understand and remember the medical concepts by self-learning approach.